Mikroefekty skali w dynamice ośrodka ciągłego - K. Wilmański (Engineering Transactions)
The present paper contains an analysis of the equations of a body with microstructure. By applying the variational method the set of equations in displacements is derived, in which remote action of microelements is accounted for. It is assumed in addition that the microstructure can undergo homogeneous deformation only. The results obtained furnich a convenient method for describing microeffects of scale for materials with natural and artificial (forced) microstructure. In addition to the analysis of these effects for the nonlinear problem the paper contains linearized equations in displacements which are discussed from the same point of view.